The wolf wilder - Rundell, Katherine (New York : Simon & Schuster Books for Young Readers, 2015)
In the days before the Russian Revolution, twelve-year-old Feodora sets out to rescue her mother when the Tsar's Imperial Army imprisons her for teaching tamed wolves to fend for themselves.
Keywords: Wolves -- Fiction; Mothers and daughters -- Fiction; Russia -- History -- Nicholas II, 1894-1917 -- Fiction; Wolves -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Survival -- Juvenile fiction; Russia -- History -- Nicholas II, 1894-1917 -- Juvenile fiction